White matter hyperintensities are associated with subthreshold amyloid accumulation - Moscoso, Alexis; Rey-Bretal, David; Silva-Rodríguez, Jesús; Aldrey, Jose M.; Cortés, Julia; Pías-Peleteiro, Juan; Ruibal, Álvaro; Aguiar, Pablo (NeuroImage (Orlando, Fla.), 2020)
The association between white matter hyperintensities (WMH) and amyloid accumulation over time in cognitively normal, amyloid-negative elderly people remains largely unexplored. In order to study whether baseline WMH were associated with longitudinal subthreshold amyloid accumulation, 159 cognitively normal participants from the Alzheimer’s Disease Neuroimaging Initiative who were amyloid-negative at baseline were examined. All the participants underwent a T1 and a Fluid-Attenuated Inversion Recovery MRI scan at baseline. Amyloid PET imaging was performed at baseline and follow-up visits in 2-year intervals for up to 8 years. Partial volume correction was applied for quantifying cortical Standardised Uptake Value Ratios (SUVR). The associations between global and regional WMH burden and amyloid accumulation were assessed using linear mixed models adjusted by demographic characteristics and baseline SUVR. Partial volume correction increased the measured annual rate of change (+2.4%) compared to that obtained from non-corrected data (+0.5%). There were no significant correlations between baseline WMHs and baseline subthreshold cortical amyloid uptake. In a longitudinal analysis, increased baseline cortical SUVR and increased baseline burden of global (p ​= ​0.006), frontal (p ​= ​0.006), and parietal WMH (p ​= ​0.003) were associated with faster amyloid accumulation. WMH-related amyloid accumulation occurred in parietal, frontal, and, to a lesser extent, cingulate cortices. These results remained unchanged after a sensitivity analysis excluding participants with the highest cortical SUVRs. This is the first study to identify a specific spatial distribution of WMH which is associated with future amyloid accumulation in cognitively normal elderly subjects without PET-detectable amyloid pathology. These findings may have important implications in prevention trials for the early identification of amyloid accumulation. •The relation between white matter lesions and amyloid accumulation is unclear.•Longitudinal Aβ-PET scans in Aβ-negative, normal elderly for up to 8 years.•A spatial pattern of WMH relates to amyloid accrual in Aβ-negative, normal elderly.•WMH patterns might help identify amyloid “accumulators”.